Total lower eyelid reconstruction with the combined use of the Hughes and Destro flaps - Diogo Almeida Lima (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: Lower eyelid cancers are common. Basal cell carcinoma, squamous cell carcinoma, and melanoma are responsible for 5 to 10% of all skin cancers. Complete reconstruction after excision of a tumor that creates a defect involving more than 50% of the eyelid is a challenge. Reports vary regarding the best method of reconstruction, and most available literature is in the form of case reports, leading to inconsistency in the evidence presented. Methods: This retrospective study examined the medical records to evaluate the functional results achieved by the author in patients who underwent total lower eyelid reconstruction after cancer resection between May 2012 and May 2016. The Hughes myotarsoconjunctival flap was used for reconstruction of the internal lamella, and the Destro VY skin advancement flap was used for the external lamella. Results: Of 13 patients with a mean age of 72.61 years, basal cell carcinoma accounted for 11 cases. No comorbidity was observed in the flap donor areas. Contralateral symmetry and palpebral closure were achieved in 12 cases; 1 case of ectropion was successfully treated, but no other functional problems were identified. Conclusion: The combined use of the Hughes flap and Destro flap is a valuable alternative for total reconstruction of the lower eyelid and can achieve favorable functional and aesthetic outcomes with donor tissue, similar to that of resected tissue.